Rapid detection and identification of Wuchereria bancrofti, Brugia malayi, b. pahangi, and Dirofilaria immitis in mosquito vectors and blood samples by high resolution melting real-time PCR - Tongjit Thanchomnang (2018)
A simple, rapid, and high-throughput method for detection and identification of Wuchereria bancrofti, Brugia malayi, Brugia pahangi, and Dirofilaria immitis in mosquito vectors and blood samples was developed using a real-time PCR combined with high-resolution melting (HRM) analysis. Amplicons of the 4 filarial species were generated from 5S rRNA and spliced leader sequences by the real-time PCR and their melting temperatures were determined by the HRM method. Melting of amplicons from W. bancrofti, B. malayi, D. immitis, and B. pahangi peaked at 81.5±0.2°C, 79.0±0.3°C, 76.8±0.1°C, and 79.9±0.1°C, respectively. This assay is relatively cheap since it does not require synthesis of hybridization probes. Its sensitivity and specificity were 100%. It is a rapid and technically simple approach, and an important tool for population surveys as well as molecular xenomonitoring of parasites in vectors. © 2013, Korean Society for Parasitology and Tropical Medicine.